Pengaruh Atraksi dan Fasilitas Wisata Terhadap Niat Berkunjung Kembali Wisatawan Ke Pantai Air Bangis Kabupaten Pasaman Barat - Novia Febriani; Hijriyantomi Suyuthie (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
This research motivation is several problems related to employee management, namely the existence of tourists who are not interested in recommending the Air Bangis Beach tourist attraction to others because of the lack of diversity of tourist attractions, the majority of tourists are not willing to return to the Air Bangis Beach tourist attraction, the majority tourists do not make the Air Bangis Beach tourist attraction their main choice for a holiday, there is a low of educational elements at the Air Bangis Beach attraction of tourist, such as the absence of cultural tourism and a lack of tourist attractions, there are complaints from tourists about the environment where there is still a lot of rubbish strewn about, thus disturbing the beauty The view when tourists enjoy the beach, the place of worship provided in the form of a prayer room, in terms of its structure, is adequate, but it is a shame that the water is poorly maintained, there are many damaged facilities such as the pier and toilets at the Air Bangis Beach tourist attraction. Quantitative research is the methodology employed. This research employed all primary and secondary sources for data. The research participants were Air Bangis Beach guests. 396 guests made up the sample for research, it was chosen by the use of a non-probability sampling method. The instrument for getting data was a scale of Likert questionnaire that has completed validity and reliability testing. The research's data processing was done using SPSS 25.00. The research findings indicate that attractions fall into the sufficient group, which is 3.23; the variable representing tourist facilities also falls into this area, with a percentage are 3.26%; and the variable representing interest, with a percentage of 3.40. Then, the hypothesis in tourism facility research (X2) has a Beta or Coefficient of Standardized is 0.312 with T by count (6.613) and significance is 0.000 <0.05, indicating that the variable of tourist facility (X2) has a good and impact in significant on interest in returning to visit (Y). The attraction value (X1) has a Beta or Coefficient of Standardized is 0.158 with T by count (0.3338) and a significance of 0.000 <0.05. The impact of tourist amenities and sites on the desire to return, with an influence of 12.3% and an Adjusted R Square of 0.123.